A border surveillance system to sense terrorist outbreaks. (September 2021) - Vadivelan, N.; Taware, Mr. Shrikant; Chakravarthi, Mr. R. Ravi; Palagan, Dr. C. Anna; Gupta, Sanjai
Abstract: Wireless Sensor Networks (WSN) are widely used in military applications such as border surveillance. This research focuses on developing a WSN network for implementing in the India-Pakistan border. The traditional approaches used for border surveillance has challenges such as energy efficiency, low cost, latency, information integrity, computation, and communication limitations and needs manual intervention. The conventional method of employing military personnel, fences, and building bulletproof walls and excavation caves at borders are replaced by WSN based sensors, radars, surveillance cameras and Unmanned Ariel Vehicles (UAV) by creating a virtual fence. A hybrid WSN based Border Surveillance System (BSS) architecture using activation scheduling strategy for high energy efficiency, load balancing capabilities, and network lifetime increment is proposed. The proposed integrated BSS architecture reduces manual intervention to a high extent by deploying sensors radars, cameras, and UAVs in place of humans. The results show that the proposed structure and activation methodology are accurate and precise in surveillance and require less maintenance, involve low-cost deployment and provide improved reliability. The experimental analysis shows that the system outperforms the other alternatives in detecting intrusion in boundary fields and has an increased lifetime via effectively handling the network resources.